Digital health in the era of COVID-19: Reshaping the next generation of healthcare - Getachew, Emnet; Adebeta, Tsegaye; Muzazu, Seke G. Y.; Charlie, Loveness; Said, Bibie; Tesfahunei, Hanna Amanuel; Wanjiru, Catherine Lydiah; Acam, Joan; Kajogoo, Violet Dismas; Solomon, Samrawit; Atim, Mary Gorret; Manyazewal, Tsegahun (Frontiers in Public Health, 2023)
COVID-19 is one of the most deadly diseases to have stricken us in recent decades. In the fight against this disease, governments and stakeholders require all the assistance they can get from various systems, including digital health interventions. Digital health technologies are supporting the tracking of the COVID-19 outbreak, diagnosing patients, expediting the process of finding potential medicines and vaccines, and disinfecting the environment, The establishment of electronic medical and health records, computerized clinical decision support systems, telemedicine, and mobile health have shown the potential to strengthen the healthcare system. Recently, these technologies have aided the health sector in a variety of ways, including prevention, early diagnosis, treatment adherence, medication safety, care coordination, documentation, data management, outbreak tracking, and pandemic surveillance. On the other hand, implementation of such technologies has questions of cost, compatibility with existing systems, disruption in patient-provider interactions, and sustainability, calling for more evidence on clinical utility and economic evaluations to help shape the next generation of healthcare. This paper argues how digital health interventions assist in the fight against COVID-19 and their opportunities, implications, and limitations.